Modelling the interactions between herpes simplex virus type 2 and HIV: implications for the HIV epidemic in southern India. Issue 1 (8th November 2010) - Foss, Anna M; Vickerman, Peter T; Mayaud, Philippe; Weiss, Helen A; Ramesh, B M; Reza-Paul, Sushena; Washington, Reynold; Blanchard, James; Moses, Stephen; Lowndes, Catherine M; Alary, Michel; Watts, Charlotte H
Abstract : Background: The role of herpes simplex virus type 2 (HSV-2) in the HIV epidemic and the potential impact of HSV-2 suppressive therapy have previously been explored only within the context of sub-Saharan Africa. In this analysis, modelling is used to estimate the contribution of HSV-2 to HIV transmission from clients to female sex workers (FSW) in a southern Indian setting and the maximum potential impact of 'perfect' HSV-2 suppressive therapy on HIV incidence. Methods: A dynamic HSV-2/HIV model was developed, parameterised and fitted to Mysore data. The model estimated the attributable fractions of HIV infections due to HSV-2. Multivariate sensitivity analyses and regression analyses were conducted. Results: The model suggests that 36% (95% CI 22% to 62%) of FSW HIV infections were due to HSV-2, mostly through HSV-2 asymptomatic shedding. Even if HSV-2 suppressive therapy could eliminate the effect of HSV-2 on HIV infectivity among all co-infected clients, only 15% (95% CI 3% to 41%) of HIV infections among FSW would have been averted. 36% (95% CI 18% to 61%) of HIV infections among HSV-2-infected FSW could have been averted if suppressive therapy reduced their risk of HIV acquisition to that of HSV-2-uninfected FSW. Conclusions: HSV-2 contributes substantially to HIV in this southern Indian context. However, even in the best case scenario, HSV-2 suppressive therapy is unlikely to reduce HIV transmission or acquisition by more than 50% (as aimed for in recent trials), because of the limited strength of the interaction effect between HSV-2 and HIV.